Identifying central dimensions of quality of life including life-related values, preferences and functional health in older patients with cancer: a scoping review protocol - Springer, Franziska; Matsuoka, Ayumu; Obama, Kyoko; Mehnert-Theuerkauf, Anja; Uchitomi, Yosuke; Fujimori, Maiko (Frontiers in Psychology, 2024)
Background: Older patients with cancer already represent the largest proportion of cancer survivors which will further increase in the upcoming years. However, older patients are highly underrepresented in clinical research, leading to a detrimental knowledge gap. Research on important aspects of QoL and associated factors for older patients with cancer is insufficient to date.Aim: The objective of this scoping review therefore is to investigate the dimensions of quality of life (QoL) including functional health, life-relevant values and preferences in older adults with cancer across all tumor entities and health care settings. It will further identify medical, sociodemographic, psychosocial and geriatric aspects associated with QoL in the elderly and compare these with younger cancer patients and older non-cancer cases.Methods: Published articles investigating QoL dimensions and associated factors in older patients with cancer, i.e. exclusively patients >= 65 years or mean/median age >= 70 years for age-mixed samples, or that compare results of older with younger cancer patients or with older non-cancer cases will be considered for this scoping review. Older patients with cancer across all tumor entities, disease stages and health care setting will be included. PubMed and PsychINFO databases will be searched for relevant articles. Abstracts and titles will be screened for basic inclusion, and two independent reviewers will conduct a full text screening to evaluate the age criteria and decide on the final inclusion of the study. Data on study and participant characteristics, QoL dimensions and geriatric factors will be extracted using a data extraction sheet. Results will be summarized descriptively to address the objectives of this review.The findings of this scoping review will provide valuable insights into central dimensions of QoL, including values, preferences and functional health in older adults with cancer, and help to improve targeted interventions and healthcare planning.